PROBLEMS AND SOLUTIONS IN FORMING PROFESSIONAL QUALITIES IN FUTURE FINE ARTS TEACHERS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article considers the process of forming professional qualities in students as a pedagogical problem. Professional qualities are a set of personal and social characteristics that students need to succeed in their profession and have a significant impact on their future professional activities. The article discusses the current pedagogical problems of forming professional qualities, the difficulties in guiding students to a profession, and the role of teachers.